Aconselhamento em HIV/aids às gestantes: percepções de enfermeiros da saúde da família - Costa, Kemily Benini (Universidade Federal de São Carlos, 2021)
Background: The feminization of the HIV epidemic not only reveals gender vulnerability, but is reported in the vertical transmission of the disease. In order to ensure effective prevention to infection, HIV/aids counseling for pregnant women proves indispensable and presents as expanded practice based on health education, vulnerability assessment and emotional support. Based on the bond and dialogue aims to regain the autonomy and protagonism of women, in the recognition of subjectivities and transformations of the defined reality, protection against the virus and comprehensive care. Objective: Analyze the perceptions of Family Health nurses about HIV/aids counseling for pregnant women. Method: This is a qualitative research based on two stages, mapping of scientific productions (scope review) and fieldwork carried with twelve Family Health nurses from three cities in the interior of São Paulo. Data were collected by semi-structures interviews and interpreted by content analysis. Results: Three categories of analysis were constructed: 1. Centrality of counseling and testing anti-HIV, in dependence and restriction of this practice to exam and conceptual theoretical limitations that characterize it. 2. Pregnancy and HIV: outcome of a positive result, evidenced by the discomfort and insecurity in communicating the diagnosis and the empirical complexity that involves a pregnant woman living with HIV. 3. Facilities, difficulties and challenges in HIV counseling for pregnant women which extends from bond and condition of being pregnant to structural challenges and constant interruptions during counseling. Considerations: Perceptions of HIV/aids counseling focuses, above all, on rapid test for detection virus and reagent result for infection. Denotes an important gap in expanded internalization of this practice and the constraint highlighted in its development. Although conflicting feelings modulate specific aspects of counseling, affirmative feelings have been related to it, enhancing the construction of new perceptions compatible with the theme's naturalization.
HIV/aids counseling to preganant women: perceptions of family health nurses
Keywords: Aconselhamento; HIV; Gestantes; Atenção Primária à Saúde; Counseling; Pregnant women; Primary Health Care; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA